Torch Lake 1985 Netting Survey Summary - Michigan Department of Natural Resources (2013)
Partial OCR done. Partially handwritten. 11 pages total. This survey was initiated to evaluate the stocking of yearling lake trout in Torch Lake. Since 1976 all planted lake trout have been marked by fin clipping. In October 1975 the fish population of Torch Lake, Antrim County was surveyed with standard Great Lakes gill net gangs, which contained the same mesh sizes as the 1975 survey, but were only one half as long (500 feet in 1985 as opposed to 1000 feet in 1975). The index stations established in 1975 were the set locations used in 1985. Lake trout (76.8% catch by weight) followed by whitefish and cisco were the most abundant fish species collected in this survey. The planted lake trout are making a significant contribution to the lake trout population of Torch Lake.